‘Paphos’ sur les monnaies depuis le ivème siècle av. J.-C. - Anne Destrooper-Georgiades (Ksiegarnia Akademicka Publishing, 2013)
The word ‘Paphos’ emerged as early as the 7th century BC and was subsequently written in varying manners, firstly on inscriptions and later in literary texts. Yet it is only from about the second half of the 4th century BC that it appears inscribed on coins, solely in Greek alphabetic characters. The word is abbreviated to one, two or four letters, which sometimes form a monogram. On the extremely rare silver coins of the last king of Paphos, Nikokles, Paphos is written in a related form, ΠAΦIΟΝ and the exact meaning of this word will be considered in this paper. A further legend, ΠΒA, written behind the neck of a crowned female head on these late coins and the identification of the head itself have prompted several differing interpretations. The exceptional crown of this figure, the legend and the depiction as a whole will be studied within the political, historical and religious context of Paphos.